IF IT WALKS LIKE A PROVERB AND TALKS LIKE A QUESTION : PROVERBIAL AND OTHER FORMULAIC INTERROGATIVES - Haas, Heather A. (Proverbium - Yearbook, 2013)
Although a small number of question-form phrases have been included in standard proverb dictionaries or have been proposed for inclusion in future dictionaries, many of these phrases, although fixed in form, lack the truth-statement function that typifies most so-called true proverbs. This is also true of sarcastic interrogatives; although sarcastic interrogatives are (at least in some cases) fixed-form interrogatives, they do not state generalizable truths about the world or propose appropriate ways to respond to particular types of recurrent situations within it. Fixed-form rhetorical questions with a more clearly proverbial function do exist, however, and a number of these proverbial interrogatives are here identified, described, and distinguished from other types of formulaic interrogatives.